The irruption of mechanics in the chemistry of life De l'irruption de la mécanique dans la chimie du vivant - Mège, René Marc; Ladoux, Benoit (M S-Medecine Sciences, 2018)
Mechanical constraints are recognized as a key regulator of biological processes, from molecules to organisms, throughout embryonic development, tissue regeneration and in situations of physiological regulation and pathological disturbances. The study of the influence of these physical constraints on the living, in particular on the cells and the organisms of the animal kingdom, has been the object for a decade of important work carried out at the interface between biology, physics and mechanics, constituting a new discipline: mechanobiology. Here we briefly describe the remarkable advances in understanding how cells and tissues both generate and perceive mechanical stresses, and how these constrains dictate cell shape, migration, cell differentiation and finally adaptation of tissues to their environment during morphogenesis, injury and repair.
CRIS-Team Scopus Importer:2024-02-19